THE EFFECT OF ENTREPRENEURIAL LITERACY, DIGITAL LITERACY AND SOCIAL MEDIA USE ON THE ENTREPRENEURIAL INTEREST OF HIGH SCHOOL STUDENTS - Paramitasari, Niken; Emilia, Putri; Yusendra, M. Ariza Eka; Asnusa, Soraya (Univesitas Muhammadiyah Tangerang, 2024)
Entrepreneurship programs at the high school level encourage students to become entrepreneurs. However, based on data on students' interest in entrepreneurship, after graduating students prefer to continue their studies or work. In addition, in the era of increasingly growing digitalization and the rise of social media as a platform for entrepreneurship, some students are not used for entrepreneurial activities, but rather for socializing, watching, etc. The school is trying to realize the young entrepreneurs starting from high school graduation through various variables. Therefore, this research aims to examine the influence of entrepreneurial literacy, digital literacy, and media use social impact on high school students' entrepreneurial interest. This research used quantitative research with a causality and associative approach used SEM-PLS. Result showed that entrepreneurial literacy, digital literacy, and media use of social media have an effect on interest in entrepreneurship. Through students' entrepreneurial literacy are expected to be able to identify problems and find creative and innovative business ideas. Digital literacy knowledge directs students to be able to identify real data and access the resources needed to support the business. Social media can be a very effective tool for networking with professionals, promoting products or services, and reaching more markets wide.